2016
DOI: 10.1158/0008-5472.can-15-3091
|View full text |Cite
|
Sign up to set email alerts
|

Improved Survival of HER2+ Breast Cancer Patients Treated with Trastuzumab and Chemotherapy Is Associated with Host Antibody Immunity against the HER2 Intracellular Domain

Abstract: The addition of trastuzumab to chemotherapy extends survival among patients with HER2+ breast cancer. Prior work showed that trastuzumab and chemotherapy augments HER2 extracellular domain (ECD)-specific antibodies. The present study investigated whether combination therapy induced immune responses beyond HER2-ECD and, importantly, whether those immune responses were associated with survival. Pre-treatment and post-treatment sera were obtained from 48 women with metastatic HER2+ breast cancer on NCCTG (now All… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 29 publications
1
58
0
1
Order By: Relevance
“…This data further support the concept that trastuzumab monotherapy can enhance a functional antitumour immunity that results in augmented tumour responses [43]. This potentially underscores the clinical importance of the host immune response in this breast cancer subtype.…”
Section: Discussionsupporting
confidence: 80%
“…This data further support the concept that trastuzumab monotherapy can enhance a functional antitumour immunity that results in augmented tumour responses [43]. This potentially underscores the clinical importance of the host immune response in this breast cancer subtype.…”
Section: Discussionsupporting
confidence: 80%
“…Since that time, several endogenous antibodies that are reactive against well-described and conserved shared tumor antigens have been identified, including antigens on RCC (4044). For example, Knutson et al 2016 recently showed that for HER2+ breast cancer patients, a combination therapy that included chemotherapy together with trastuzumab (mAb against HER2) induced, in 69% of patients, endogenous IgG-antibodies directed against HER2 and a subset of endogenous shared tumor-associated antigens; this endogenous antibody response was associated with improved disease outcome (45). However, for most tumor types, methods to readily demonstrate and quantify the presence and functional activity of endogenous antibodies against the unique neo-antigens present on patients’ autochthonous tumors, for the full cohort of patients enrolled in a trial such as this one, remain elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Adaptive immunity has also been shown to play a role in mediating breast cancer cell lysis by trastuzumab in murine models, with CD8 + and CD4 + T cell depletion resulting in a blunted response to treatment with trastuzumab (6,7). In patients with metastatic HER2-positive breast cancer, trastuzumab has been shown to induce anti-HER2 CD4 + T cell responses as well as anti-HER2 antibody responses with anti-HER2 antibody responses being associated with improved progression-free and overall survival (8,9). In addition, trastuzumab-treated breast cancer cells are more susceptible to killing by antigen-specific cytotoxic T lymphocytes (CTLs) due to increased internalization of HER2 and presentation of HER2-derived peptides on MHC class I molecules (10).…”
Section: Introductionmentioning
confidence: 99%